LITERASI DIGITAL BERBASIS PENDIDIKAN ISLAM MELALUI PENDAMPINGAN ORANG TUA DI SOKANANDI BANJARNEGARA - Lina Sulistiani; Ngarifin Shiddiq; Ahmad Khoiri (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2021)
This study aims to determine 1). parents' perceptions of strengthening digital literacy based on Islamic education for children in Sokanandi Village RT 02 RW 02 Banjarnegara Regency, 2). knowing parents' strategies in strengthening digital literacy based on Islamic education for children, and 3). find out what are the supporting and inhibiting factors for parents in strengthening digital literacy based on Islamic education for children. This type of research is field research or field research with a qualitative approach. The data sources used came from the heads of sub-districts, heads of RTs, parents, children, and data from Sokanandi Village, RT 02 RW 02, Banjarnegara Regency. To obtain the necessary data the authors use documentation techniques, in-depth interviews and participant observation. Data analysis was carried out through the process of data reduction, data presentation and drawing conclusions. The results of the research analysis show 1). some parents' perceptions about strengthening digital literacy based on Islamic education for children, namely the internet and digital media helping Islamic religious subjects; planting Islamic education through digital literacy becomes more effective and easier; guidance on digital literacy based on Islamic education is considered important so that children can choose educational sites and applications; the use of digital media must be limited so that it is not excessive and becomes addictive; and many emerging trends of new language that is less polite. 2). The parent assistance strategy is carried out by accessing references to Islamic religious subjects on the internet; watching Islamic content with children; interactive dialogue during digital media use and after; gadget usage time management; civilized control of conversational language on social media. 3). Factors supporting parents in strengthening digital literacy based on Islamic education are children's skills that are responsive and easy to develop; lots of Islamic educational content available on the internet; awareness, concern, and responsibility of parents in educating children; cooperation between both parents; exemplary parents in communicating in the family. While the inhibiting factors are limited time and parental knowledge about digital literacy and Islamic education; wasteful internet quota; the older the child, the more difficult it is to be directed because they tend to want to be independent; and children's circle of friends, not all of which are good.